Software para análise da cinética do consumo de oxigênio durante exercício moderado - Beltrame, Thomas (2012)
The characterization of behavior of some biological variables in the transition restexercise (on-transition) seems to help understand how the organism adjusts some physiological systems in the beginning of physical exercise. Among these variables, the kinetics of oxygen consumption (VO2) is widely studied and can add information about physical fitness. The objective of this study was to develop new software that facilitates the characterization of the VO2 kinetics in on-transition of constant work load exercise. Some tests with the software, performed in ten healthy male subjects, showed no statistical differences between the values of the kinetics´ s parameters found by the new software and the parameters obtained by SigmaPlot software. Additionally, the Interface facilitates analysis of the kinetics of VO2. The conclusion from this study shows that this new software may be used as a simple tool to characterize the behavior of VO2. Now, the use of VO2 kinetics can be used by a larger number of health care professionals who aim to this type of analysis.